Baseline mechanisms for IT governance at universities - Bianchi, I.; Sousa, R.; Pereira, R.; Hillegersberg, J. (Proceedings of the 25th European Conference on Information Systems (ECIS), 2017)
The pervasive use of technology has created a critical dependency on Information Technology (IT) that requires IT Governance (ITG). ITG calls for the definition and implementation of formal mechanisms at the highest level in the organization taking into account structures, processes and relational mechanisms for the creation of business value from IT investments. However, determining the right ITG mechanisms remains a complex endeavour. Previous studies have identified ITG mechanisms in use in the financial and health care industries. While universities also increasingly depend on IT for their success, ITG implementation in universities has not received much attention. As universities have many unique characteristics, it is highly unlikely that ITG experiences from the financial and health care industries can be directly applied to universities. Therefore, the purpose of this research is to identify an ITG mechanisms’ baseline for universities. Six case studies comprising of in-depth interviews three international universities in Brazil, Portugal and the Netherlands, led to the proposal of a minimum ITG baseline for universities that is comparared with the financial and health care industries. This article concludes by presenting key contributions, limitations and future work.